PERAN KELOMPOK NELAYAN DALAM PENINGKATAN TARAF HIDUP MASYARAKAT PESISIR DI LOMBOK - Rahmawati, Ratih; Ramdani, Taufiq; Juniarsih, Nuning (UNIVERSITAS SEBELAS MARET (UNS), 2023)
Coastal areas have potential, one of which is marine tourism, so efforts are needed to develop coastal areas into tourist attractions and productive economic businesses. However, there is a decrease in the number of human resources who are interested in becoming fishermen. Similarly, what happened on the Lombok Island, the quantity of human resources in stabilizing production in coastal area governance decreased, thus affecting the quality of coastal area development which affected the community's economy. Therefore, fishing groups play an important role in improving people's living standards. This research is a qualitative research using a case study approach analyzed by James Scott's theory of subsistence ethics. The component analyzed is the social situation in coastal communities located on the Lombok. The result of the study is that coastal communities improve living standards through the role of fishermen groups as follows the following fishermen's group activities that are beneficial for the development of the quality of marine products catches, carries out activities held by local governments and utilizes assistance distributed in groups, fishermen group members can carry out self-development by exchanging experiences and information between fellow fishermen, provide mutual assistance and support when in difficulties, on the other hand, have an awareness of the importance of education for their children so that they continue to strive to improve their lives. Keywords: Fisherman Group, Potential Coastal Area, Standard Of Living, Coastal Community. AbstrakWilayah pesisir memiliki potensi salah satunya adalah wisata bahari sehingga perlu upaya pengembangan daerah pesisir menjadi obyek wisata dan usaha ekonomi produktif. Namun, terdapat penurunan jumlah sumber daya manusia yang berminat untuk menjadi nelayan. Begitu pula yang terjadi di Pulau Lombok, kuantitas sumber daya manusia dalam stabilisasi produksi tata kelola wilayah pesisir menurun sehingga berpengaruh pula pada kualitas pengembangan wilayah pesisir yang berpengaruh pada perekonomian masyarakat. Oleh karena itu, kelompok nelayan berperan penting dalam meningkatkan taraf hidup masyarakat. Penelitian ini adalah penelitian kualitatif menggunakan pendekatan studi kasus yang dianalisis dengan teori etika subsistensi James Scott. Komponen yang dianalisis adalah situasi sosial pada masyarakat pesisir yang berlokasi di Pulau Lombok. Hasil penelitian adalah masyarakat pesisir meningkatkan taraf hidup melalui peranan kelompok nelayan sebagai berikut: masyarakat pesisir aktif mengikuti kegiatan kelompok nelayan yang bermanfaat bagi pengembangan kualitas tangkapan hasil laut, melaksanakan kegiatan yang diadakan oleh pemerintah daerah dan memanfaatkan bantuan yang disalurkan secara berkelompok, anggota kelompok nelayan dapat melakukan pengembangan diri dengan bertukar pengalaman dan informasi antar sesama nelayan, saling memberikan bantuan dan dukungan apabila berada dalam kesulitan, disisi lain memiliki kesadaran akan pentingnya pendidikan putra-putrinya sehingga terus berupaya untuk meningkatkan taraf hidup. Kata Kunci: Kelompok Nelayan, Potensi Wilayah Pesisir, Taraf Hidup, Masyarakat Pesisir.